The Effect of Motivation and the Entrepreneurial Mentality on Accounting Student's Interest for Entrepreneurship (Case Study on Accounting Students in the University of Dehasen Bengkulu) - Yutri Lisarah; Sulisti Afriani; Ida Ayu Made Er Meytha Gayatri (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of motivation and entrepreneurial mentality on accounting students' interest in entrepreneurship. Interest in entrepreneurship is a sense of preference and a sense of interest in a thing or activity, without anyone telling. In conducting research, the researcher uses the survey method. Based on the Slovin formula, the research sample obtained is 50 people from a total population of 102 people using the accidental sampling method. To find out the interest in entrepreneurship in accounting students at the University of Dehasen Bengkulu, the researcher used a questionnaire distributed via google form. The results show that: 1). Motivation has a positive and significant effect on entrepreneurial interest as indicated by the value of t-count > t-table (3.780 > 2.012). 2). Entrepreneurial mentality has a positive and significant effect on interest in entrepreneurship as indicated by the value of t-count > t-table (4.753 > 2.012). 3). Entrepreneurial motivation and mentality have a positive and significant effect together on interest in entrepreneurship as indicated by the F-count > F-table (61.378 > 3.20).